040 Colour-dependent modulation of the pupillary light reflex: interaction with clonidine. Issue 10 (24th September 2010) - Szabadi, E; Biswas, A; Langley, R W; Bradshaw, C M
Abstract : Aims: Short-wave length (blue) light is more effective in evoking the pupillary light reflex than long-wave length (red/orange) light, due to the stimulation of melanopsin-containing photoreceptors on retinal ganglion cells by blue light. The á2-adrenoceptor agonist clonidine "switches off" central noradrenergic neurones, thus reducing sympathetic outflow to the iris. We compared the effects of clonidine on "blue" and "orange" pupillary responses. Methods: Sixteen healthy male volunteers participated, double-blind, in two (clonidine 0.2 mg, placebo) sessions. The right pupil was stimulated with blue (472 nm) and orange (607 nm) light pulses (30 s) matched for intensity (10, 100, 1000 Cd m-2), and initial (maximum constriction during first 2 s) and sustained (mean constriction during subsequent 28 s) responses were measured. Alertness and autonomic functions were also assessed. Data were analysed with ANOVA; significance criterion p<0.05. Results: Blue light evoked larger responses than orange light. Clonidine equally enhanced sustained pupil constriction to blue and orange light, whereas it had no effect on initial constriction. Clonidine reduced alertness, salivation and blood pressure, consistent with its sedative and sympatholytic effects. Conclusions: The enhancement of sustained pupil constriction to light by clonidine indicates synergism between the sympatholytic effects of light and clonidine. The equal effect of clonidine on "blue" and "orange" responses is consistent with the view that both responses are channelled via the same route, that is melanopsin-containing ganglion cells.